International perspectives on knowledge integration : theory, research, and good practice in pre-service teacher and higher education - Lehmann, Thomas (Postdoctoral researcher) (Leiden ; Boston : Brill Sense, 2020)
"Interest in knowledge integration grew considerably in recent years, particularly within the realm of pre-service teacher education. However, studies on the topic conceptualize knowledge integration in diverse ways. For example, it may be conceived as a specific coherence-building learning process which involves not only acquiring but interrelating knowledge of different types (e.g., theoretical and practical) or from different domains, which together constitute a teacher's or educational specialist's professional knowledge base (e.g., content knowledge, pedagogical knowledge, pedagogical content knowledge, knowledge about using technologies for learning and instruction, etc.). Furthermore, knowledge integration also refers to the meaningful application of knowledge of different types and from various domains in order to act professionally and to teach successfully. In many countries, however, future teachers and educational specialists often struggle with knowledge integration, because the task of integrating knowledge across domains, from various courses, and from practical training is left largely to the individuals. Thus, the efficacy and quality of higher education programs, particularly in pre-service teacher education, could be improved through careful attention to knowledge integration. International Perspectives on Knowledge Integration aims at facilitating the consideration of knowledge integration in teacher training and higher education in both research and practice. Specifically, it explores theoretical conceptions and methods, and reports on original research and good practices for fostering knowledge integration. It is thus of interest to researchers, faculty board members, and lecturers concerned with teacher training and higher education, as well as to student-teachers and students of pedagogy, education, and educational psychology"--
What is knowledge integration of multiple domains and how does it relate to teachers' professional competence? / Thomas Lehmann -- Conceptualizing (pre-service) teachers' professional knowledge for complex domains : the case of technology and heterogeneity / Karsten Krauskopf, Carmen Zahn and Friedrich W. Hesse -- Searching for the key to knowledge integration : a lens to detect the promotion and use of integrated knowledge / David D. Barker, Matthew S. Winsor, J. Vince Kirwan and Theodore J. Rupnow -- Fostering professionalism and scientificity through integration of disciplinary and research knowledge / Katrin Klieme, Thomas Lehmann and Florian Schmidt-Borcherding -- Processes of knowledge integration between realms of pedagogical content knowledge and how to capture them / Anita Stender and Maja Brückmann -- Knowledge and structure to teach : a model-based computer-linguistic approach to track, visualize, compare and cluster knowledge and knowledge integration in pre-service teachers / Pablo Pirnay-Dummer -- Separative and integrative learning in teacher education : validity and reliability of the "SILTE" short scales / Thomas Lehmann, Katrin Klieme and Florian Schmidt-Borcherding -- Pedagogical and psychological content in teacher education : exploring synergies between educational foundation courses and subject courses in university-based education / Hendrik Lohse-Bossenz, Andrea Westphal and Miriam Vock -- Using relevance instructions to support the integration of teacher knowledge / Helene Zeeb, Eileen Spitzmesser, Alisa Röddiger, Timo Leuders and Alexander Renkl -- Closing the gap : an innovative learning environment for enabling pre-service teachers to put theoretical knowledge into action / Hans-Peter Gottein -- Adaptive cycles of teaching : exploring pre-service teacher learning through teaching / Diane Salmon, Eun Kyung Ko, Ruth Freedman and Jill Zifkin -- Coherence within teacher education : Swedish lessons / Jonathan Lilliedahl, Tom Wikman and Sven-Erik Hansén -- Effects of game-based learning in teams on knowledge integration : mental models at work / Norbert M. Seel -- Promoting knowledge integration in teacher education programs : an example from secondary mathematics teacher education / Matthew S. Winsor, David D. Barker and J. Vince Kirwan -- The linkage of research and writing competence in teacher education / Sandra Moroni and Gisela Bürki -- Teacher educators and pre-service teachers work towards knowledge integration : making authentic links in classroom pedagogy / Ruth Reynolds, Suzanne Macqueen and Kate Ferguson-Patrick.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on September 30, 2020).
eBooks on EBSCOhost
Keywords: Teachers -- Training of; Knowledge, Theory of; Enseignants -- Formation; Théorie de la connaissance; epistemology; Knowledge, Theory of; Teachers -- Training of; Electronic book